Sex differences in claimed and behavioral self-handicapping and ADHD symptomatology in emerging adults - Jaconis, Maryanne; Boyd, Stephen J.; Hartung, Cynthia M.; McCrea, Sean M.; Lefler, Elizabeth K.; Canu, Will H. (Attention deficit and hyperactivity disorders, 2016)
Although the research is clear that boys with ADHD have higher symptomatology and impairment than girls with ADHD, for adults the research is mixed. Some studies suggest no sex differences, whereas others suggest that women might have higher symptomatology and impairment. The present study examined sex differences in ADHD symptomatology and impairment, and the possible role of claimed and behavioral self-handicapping as an explanation for any differences. Claimed self-handicapping (CSH) involves reports of performance-inhibiting conditions, whereas behavioral self-handicapping (BSH) involves reporting more objective, intentional acts that could undermine performance. College students ( N = 699) completed an online study. Sex differences were found for hyperactivity such that women reported higher levels, but not for inattention or impairment. The test of the indirect effect of sex through CSH was significant, suggesting that higher levels of CSH in women were associated with elevated ADHD symptoms and impairment. The test of the indirect effect of sex through BSH was also significant, suggesting that higher levels of BSH in men are associated with elevated symptoms of ADHD and impairment. These data extend the literature by suggesting that self-handicapping might at least partially explain differential self-reporting of ADHD symptoms and impairment in emerging adults across the sexes.